2020
DOI: 10.1177/0267659120937906
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenator impact on voriconazole in extracorporeal membrane oxygenation circuits

Abstract: Introduction: To determine the oxygenator impact on alterations of voriconazole in a contemporary neonatal/pediatric (1/4 inch) and adolescent/adult (3/8 inch) extracorporeal membrane oxygenation circuit including the Quadrox-i® oxygenator. Methods: Simulated closed-loop extracorporeal membrane oxygenation circuits (1/4 and 3/8 inch) were prepared with a Quadrox-i pediatric and Quadrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 15 publications
1
24
1
Order By: Relevance
“…Literature describing the exposure to voriconazole during ECMO is limited to three ex vivo studies and six case reports [ 11 , 12 , 15 , 18 , 19 , 20 , 21 , 22 , 23 ]. The ex vivo studies demonstrated significant voriconazole losses in ECMO circuits, even up to 80% in some reports [ 11 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Literature describing the exposure to voriconazole during ECMO is limited to three ex vivo studies and six case reports [ 11 , 12 , 15 , 18 , 19 , 20 , 21 , 22 , 23 ]. The ex vivo studies demonstrated significant voriconazole losses in ECMO circuits, even up to 80% in some reports [ 11 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Literature describing the exposure to voriconazole during ECMO is limited to three ex vivo studies and six case reports [ 11 , 12 , 15 , 18 , 19 , 20 , 21 , 22 , 23 ]. The ex vivo studies demonstrated significant voriconazole losses in ECMO circuits, even up to 80% in some reports [ 11 , 21 , 22 ]. However, in these studies, patient and disease related factors, such as metabolism, elimination, inflammatory mediators, altered pH and concomitant drugs, were not accounted for [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations